The Effect of Barrier Use on Population Development and Attacks of B.tabaci Genn. on Soybean Plantations: Pengaruh Penggunaan Barrier Terhadap Perkembangan Populasi dan Serangan B.tabaci Genn. pada Pertanaman Kedelai - Muhvidatul Jannah; Nanang Tri Haryadi (Universitas Merdeka Madiun, 2024)
Soybean (Glycine max (L) Merrill) is one of the food crop commodities in Indonesia. Soybean crop productivity decreased due to one of them being attack of B. tabaci Genn. One of the ways for controlling B. tabaci Genn. pests in soybean cultivation is by using a barrier. Barrier is an integrated pest management (IPM) which is based on ecological balance in nature. Pests are prevented from coming and attacking crops by using various forms of barriers that can slow down the movement of pests. The use of barriers can be a useful tool to reduce the development of B. tabaci Genn. on planting. This study was conducted to determine the effect of using a barrier on the population and attack of B. tabaci Genn. The barriers used in this study are plastic barriers, organdy barriers, sunflower barriers, and corn plant barriers. The study used a randomized block design with 5 treatments, namely P1 = control, P2 = organdy barrier, P3 = sunflower barrier, P4 = corn plant barrier and P5 = plastic barrier. The data obtained were then analyzed using ANOVA variance and further tested using the DMRT test at 5% level. The observed variables were population and attack intensity on B. tabaci Genn. in soybean planting areas, visits by other pests and soybean yields.